The effect of orthodontic treatment on smile attractiveness: a systematic review. - Coppola, G..; Christopoulou, I..; Gkantidis, N..; Verna, C..; Pandis, N..; Kanavakis, G.. (Tufts University. Tisch Library., 2023)
Springer Open.